THE STYLES OF SPECIAL ARTISTRY IN RHYTHMIC GYMNASTICS - Krafte, Diana; Lāriņš, Viesturs; Fernāte, Andra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Rhythmic gymnastics is a high achievement sport that requires athletes to demonstrate maximal abilities of the human body control while performing imaginative and meaningful compositions. With increasing of the technical complexity of the competitive compositions and striving for high results, less attention is paid to performance aesthetics. But at the same technical level during the competition, a decisive role in the gymnasts' performance is given to aesthetics. Patterns in the choice of composition content and gymnasts’ appearance and emotional similarities during performance allow concluding that there is a certain style, which can be defined as a special artistry style in rhythmic gymnastics. The aim of the research is to develop theoretical model of special artistry in rhythmic gymnastics, setting the tasks to determine, classify, structure, describe with determined artistic criteria and visualize with artistical images the special artistry styles. To develop the model the method of scientific and special literature analysis, audiovisual source analysis and modeling method were used. The model is mainly relying on C.G. Jung's theory of human perception of the world through universal symbols and the primary archetypes of the collective unconscious. Since mainly women participate in rhythmic gymnastics, the determination of the special artistry styles was based on the women archetypes of Ancient Greece goddesses according to the psychoanalyst prof. J.S. Bolen. To illustrate the styles more than 400 audiovisual materials were researched. As a result, the theoretical special artistry 32–style model in rhythmic gymnastics with two matrices of opposite style expressions consisting of 16 images each was created.